SIKAP PEMILIK LAHAN TERHADAP ALIH FUNGSI LAHAN DI DESA KALASEY SATU - Saiful ., Sarayar; Rine ., Kaunang; Mex L. Sondakh (Sam Ratulangi University, 2016)
This study aims to determine the attitude of landowners against land conversion in the village Kalasey One, Minahasa. This research was conducted by using primary data obtained from interviews on a sample of attitudes concerning land owners who've experienced over the land by using a questionnaire that has been prepared. Secondary data were obtained from the Office of the Central Statistics Agency (BPS) and the Office of Manado City Government Kalasey Village One. The results showed that the attitude of landowners against land conversion mostly to take place quickly and the conversion is done by first over land tenure. Land converted generally used to build houses and residential areas. Factors that cause land conversion categorized into internal factors such as the pressing economic needs and the desire to change the fate, as well as external factors such as population growth and government policies. Meanwhile land use also has a positive effect, namely the presence of housing construction resulted in the development of rural economy. The attitude of landowners against land conversion is at an index number of 73.73 percent means included in either category.